The Influence of Corporate Governance Criteria, Accounting Conservatism, Sales Growth and Firm Size on Investment Efficiency - Rosalina, Eka; Lukviarman, Niki; Hamidi, Masyhuri; Adrianto, Fajri (Ilomata International Journal of Management, 2025)
This study investigates the effect of corporate governance, accounting conservatism, firm size, and sales growth on investment efficiency. A multiple linear regression model was employed using SPSS for data analysis. The study covers the period from 2013 to 2023 and focuses on non-cyclical consumer sector companies, with a total sample of 379 observations. The data were obtained from the financial statements of companies listed on the Indonesia Stock Exchange (IDX). Investment efficiency was measured using the proxy developed by (Richardson, 2006), which relates free cash flow to the level of overinvestment at the firm level. Corporate governance was proxied by the proportion of independent board members and board size, while accounting conservatism was assessed through the quality of financial reporting. Firm size was measured using the natural logarithm of total assets, and sales growth was assessed using the growth rate of sales. The research results show that corporate governance, as measured by board independence and board size, influences investment efficiency, with the board fulfilling its obligations effectively. Accounting conservatism also influences investment efficiency, as a result of the concept of prudence in investment decisions. Sales growth and company size also have no effect on investment efficiency due to excessive leverage.